Prehospital Epinephrine Use in Pediatric Anaphylaxis by Emergency Medical Services. Issue 8 (13th August 2022) - Lowing, Dena; Chung, SunHee; Luk, Jeffrey; Dingeldein, Leslie
Abstract : Objectives: Anaphylaxis requires prompt assessment and management with epinephrine to reduce its morbidity and mortality. This study examined the prehospital management of pediatric anaphylactic reactions in Northeast Ohio. Methods: This is a retrospective chart review using emergency medical service (EMS) run charts of patients 18 years and younger from February 2015 to April 2019. Patient charts with the diagnosis of "anaphylaxis" or "allergic reaction" were reviewed and confirmed that symptoms met anaphylaxis criteria. Information regarding epinephrine administration before EMS arrival and medications given by EMS providers was collected. Analysis was performed using descriptive statistics. Results: From 646 allergic/anaphylactic reaction EMS run charts, 150 (23%) met the guideline criteria for anaphylaxis. The median patient age was 12 years. Only 57% (86/150) of these patients received intramuscular epinephrine, and the majority received it before EMS arrival. Epinephrine was administered by EMS to 32% (30/94; 95% confidence interval [CI], 22.7% to 42.3%) of patients who had not already received epinephrine. The odds of receiving prehospital epinephrine were significantly lower for patients 5 years and younger (risk difference [RD], −0.23; 95% CI, −0.43 to −0.04), those with no history of allergic reaction (RD, −0.20; 95% CI, −0.38 to −0.03), those who presented with lethargy (RD, −0.43; 95% CI, −0.79 to −0.06), and those whose trigger was a medication or environmental allergen (RD, −0.47; 95% CI, −0.72 to −0.23 for each). Conclusions: Emergency medical service providers in this region demonstrated similar use of epinephrine as reported elsewhere. However, 43% (64/150) of pediatric patients meeting anaphylaxis criteria did not receive prehospital epinephrine, and 10% (15/150) received no treatment whatsoever. Efforts to improve EMS provider recognition and prompt epinephrine administration in pediatric cases of anaphylaxis seem necessary.